2021
DOI: 10.1111/jori.12353
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk aversion in two periods: An application to self‐insurance and self‐protection

Abstract: Risk management decisions provide a means to elicit individuals' risk preferences empirically. In such a context, the literature often presumes that the decision to invest in risk management and the benefit of this investment occur contemporaneously. There is, however, no consensus in the theoretical literature that one-period results can be transferred to intertemporal settings. To address this gap, we study the effect of an increase in risk aversion on the demand for risk management in a two-period context. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…(1999) and others (see the exhaustive review in Courbage et al., 2013). A similar result was confirmed by Menegatti (2009) and Huber (2022) for a two‐period model. This probability threshold that determines if self‐protection increases or decreases with risk aversion is considered endogenous in the sense that it depends jointly on the preferences of both the benchmark agent and the “more risk averse” agent involved in the comparison.…”
Section: Preferences Towards Risk and Self‐protection Under Health Ri...supporting
confidence: 83%
See 2 more Smart Citations
“…(1999) and others (see the exhaustive review in Courbage et al., 2013). A similar result was confirmed by Menegatti (2009) and Huber (2022) for a two‐period model. This probability threshold that determines if self‐protection increases or decreases with risk aversion is considered endogenous in the sense that it depends jointly on the preferences of both the benchmark agent and the “more risk averse” agent involved in the comparison.…”
Section: Preferences Towards Risk and Self‐protection Under Health Ri...supporting
confidence: 83%
“…After Dionne and Eeckhoudt (1985), showed that self-protection, contrary to self-insurance, can decrease when risk aversion increases, a loss probability threshold over which this effect takes place has been identified in a one-period setting by Jullien et al (1999) and others (see the exhaustive review in Courbage et al, 2013). A similar result was confirmed by Menegatti (2009) and Huber (2022) for a two-period model. This probability threshold that determines if self-protection increases or decreases with risk aversion is considered endogenous in the sense that it depends jointly on the preferences of both the benchmark agent and the "more risk averse" agent involved in the comparison.…”
Section: Perceptionmentioning
confidence: 56%
See 1 more Smart Citation
“…If the company can manage and make good investment decisions, it will increase its profits. Investment results have a positive effect on the financial performance of the life insurance company, seen from its profit (Huber, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This supports the research by Hidayat et al (2021), which explains that premium income affects profits positively, meaning that the company's profit increases with increasing premium income. Besides receiving funds from customers, the company also must return the funds to customers (Huber, 2022). Therefore, the company will process the funds received by making investments in Sharia financial institutions.…”
Section: The Introductionmentioning
confidence: 99%